2018
DOI: 10.1093/hmg/ddy241
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting KMT2D missense mutations in Kabuki syndrome patients

Abstract: Kabuki syndrome is a rare autosomal dominant condition characterized by facial features, various organs malformations, postnatal growth deficiency and intellectual disability. The discovery of frequent germline mutations in the histone methyltransferase KMT2D and the demethylase KDM6A revealed a causative role for histone modifiers in this disease. However, the role of missense mutations has remained unexplored. Here, we expanded the mutation spectrum of KMT2D and KDM6A in KS by identifying 37 new KMT2D sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 88 publications
0
54
1
Order By: Relevance
“…We identified a deep splicing variant of KMT2D (c.14000-8C>G) in our cohort. To our knowledge, only three splicing variants of KMT2D (c.840-6delC, c.4584-6C>G, and c.10356-9G>A) have been reported to reside deeper than five nucleotides (Banka et al, 2012;Cocciadiferro et al, 2018), but no variant has been proven by RNAseq. We performed RNA-seq analysis and confirmed the presence of aberrantly spliced KMT2D mRNA in lymphocytes from the patient (Figure 2b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We identified a deep splicing variant of KMT2D (c.14000-8C>G) in our cohort. To our knowledge, only three splicing variants of KMT2D (c.840-6delC, c.4584-6C>G, and c.10356-9G>A) have been reported to reside deeper than five nucleotides (Banka et al, 2012;Cocciadiferro et al, 2018), but no variant has been proven by RNAseq. We performed RNA-seq analysis and confirmed the presence of aberrantly spliced KMT2D mRNA in lymphocytes from the patient (Figure 2b).…”
Section: Discussionmentioning
confidence: 96%
“…p.(Glu5038Lys) was not located in any of the known functional domains, but was in a specific region (amino acids 4,995-5,090) where missense mutations in KS are particularly concentrated (Faundes et al, 2019). Many missense variants of KS patients in the C-terminal region of KMT2D have been demonstrated to impair its histone H3 lysine nine methylation activity and protein complex formation (Cocciadiferro et al, 2018). Further characterization of the protein structure and functional domains of KMT2D would enable the accurate evaluation of the pathogenicity of KMT2D missense variants in the diagnostic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Focused analyses of missense variants in KMT2D have recently been published. Cocciadiferro et al () identified missense variants associated with Kabuki syndrome along the entire length of the protein and used functional studies to demonstrate that some missense variants abrogate histone methylation activity, confirming these are loss‐of‐function variants. Faundes et al () analyzed three groups of missense variants in KMT2D : 1) germline variants associated with Kabuki syndrome, 2) somatic variants found in various cancers, and 3) a compilation of “control” variants observed in ExAC (Lek et al, ) and similar databases.…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants are observed in approximately 15–20% of cases, and can occur along the entire length of the protein (Bogershausen et al, ). Recent reports have attempted to categorize these variants, which appear to cluster in specific functional domains, although their pathogenicity can be more difficult to interpret (Bogershausen et al, ; Cocciadiferro et al, ; Faundes, Malone, Newman, & Banka, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study provided evidence that some naturally occurring missense mutations in KMT2D effectively impact KMT2D interaction and H3K4 methylation activity. 17 The c.2413C > T missense variant, detected in our patient, has not been previously reported in the literature and has not been annotated in variant database (Leiden Open Variation Database [www.lovd.nl/], the PubMed database of National Center for Biotechnology Information (www.ncbi. nlm.nih.gov/), the Human Gene Mutation Database (www.…”
Section: Discussionmentioning
confidence: 97%